The dual housing market in large agglomerations: an analysis to the portuguese context - Santos, António Duarte (2022)
1. Introduction to surroundings on housing in Portugal 2. Still the effects of the 2008 crisis on real estate business and housing 3. Methodology Approach 4. The Rental Market 5. The Housing Market 6. Complementary Data Analysis 7 . Conclusions